Impact of Focal Muscle Vibration on Flaccid Upper Limb Motor Paralysis following Acute Brain Disease: A Case Study - Hirotaka Saito; Haruka Kobayashi; Kodai Oba; Yosuke Hamaya (Case Reports in Neurological Medicine)
Focal muscle vibration (FMV) is increasingly being recognized as a rehabilitative therapy for enhancing motor function in central nervous system (CNS) diseases, particularly in patients with fine motor control deficits stemming from CNS damage. Brain lesions from these diseases disrupt the motor networks, necessitating novel rehabilitation strategies. By applying vibrations to muscles, FMV stimulates sensory fibers to induce cortical activity and kinesthetic illusions. While initial studies have highlighted FMV’s role in reducing spasticity, recent evidence points to its potential in treating motor paralysis. However, prior research has been limited by the lack of acute-phase studies and a focus on patients with minimal muscle contraction capability. This report aimed to explore FMV’s efficacy on upper limb motor function in patients with flaccid motor paralysis immediately after acute CNS diseases. We report the case of a septuagenarian male with a brain abscess in the right parietal lobe, leading to flaccid motor paralysis. Rehabilitation included 28 sessions of occupational and physical therapy that incorporated FMV. Significant improvements were observed in upper extremity function, with moderate to very large effect sizes, while lower limb function showed lesser improvement without adverse effects. This case suggests the utility of FMV in enhancing upper-limb motor function after acute CNS injuries, potentially serving as a supplementary therapy for spontaneous recovery. This report contributes to emerging evidence on FMV’s benefits in acute flaccid motor paralysis, expanding the documented therapeutic scope.